Hemodiyalizdeki resirkülasyonu önlemede hemşirenin rolü - Kartal, Arzu (My University, 2009)
Çalışmanın amacı; hemodiyalizdeki resirkülasyonu önlemede hemşirenin rolünü belirlemektir. Bu çalışma, RTS Transmed Diyaliz Merkezinde hemodiyaliz tedavisi alan 141 hasta ile Eylül 2007 – Mayıs 2008 tarihleri arasında deneysel olarak yapıldı. Araştırma verileri için; sosyodemografik özellikleri, arterio-venöz (A-V) fistül bilgileri, biyokimyasal verileri, Kt/ V ve resirkülasyon oranlarını içeren “Hasta Tanıtım Formu” kullanıldı. Resirkülasyon testi için önce iki iğneli üre tekniği, daha sonrada dilüsyon tekniği kullanıldı. Dilüsyon tekniği için Crit-Line III TQA cihazı kullanıldı. İki iğneli üre tekniği uygulanan 31 hastada resirkülasyon bulunmazken dilüsyon tekniği uygulanan hastaların ikisinde resirkülasyon saptandı. Dilüsyon tekniği %47’si kadın, %53’ü erkek toplam 141 hastaya uygulandığında sekiz hastada resirkülasyon saptandı. Resirkülasyon görülme oranı %5.7 dir. Resirkülasyon saptanan hastaların iğne girişim yerleri değiştirildiğinde resirkülasyonun ortadan kalktığı belirlendi. İğne pozisyonları açısından resirkülasyon oranları arasında anlamlı fark bulundu. Ters yön ve farklı A-V damar girişimi olan hastalarda resirkülasyon görülmezken, yan yana, aynı yönde ve farklı A-V damar girişimi olan hastalarda resirkülasyon olduğu saptandı. Resirkülasyon olan hastalarda, olmayan hastalara göre daha fazla A-V fistül kaybı ve arter-ven iğnelerinin fistüle uzaklığının daha az olduğu saptandı. Resirkülasyonun önlenmesinde arter-ven iğnelerinin fistüle olan uzaklığı, iğneler arasındaki mesafe ve iğne giriş yönleri önemlidir. Damar giriş yolları, Dilüsyon tekniği, Hemodiyaliz, Resirkülasyon

THE ROLE OF THE NURSE IN PREVENTING RECIRCULATION ON HEMODIALYSIS The aim of this study was to determine the role of the nurse in preventing recirculation on hemodialysis. An experimental study was conducted in 141 patients receiving hemodialysis in RTS Transmed Dialysis Centre between September 2007 and May 2008. Identification form including socio-demographic variables arterio-venous (A-V) fistulae information, biochemical data, Kt/ V and recirculation rate was used for data collection. For recirculation test, firstly two needled urea technique and then dilution technique were used. Crit-Line III TQA device was used for dilution technique. None of 31 patients was diagnosed with the recirculation in two needled urea technique but two patients were diagnosed with the recirculation in dilution technique. When the dilution technique was applied in 47% women and 53% men of total 141 patients, eight patients were diagnosed whit the recirculation. The rate of recirculation is 5.7%. When the needle insertion point was changed in patients having recirculation, the recirculation was not diagnosed. There was a significant difference in recirculation rates according to the needle insertion point. Recirculation was not diagnosed in patients who had insertion diverse needle side and difference A-V vascular access but recirculation was diagnosed in patients who had insertion same, side to side and difference A-V needles. The more loss of fistulae and fewer intervals between A-V fistulae and needles were found in patients having recirculation than patients not having recirculation. The needle insertion point, intervals between A-V fistulae and needles, and needle position are important in preventing of recirculation. Key words: Dilution technique, Vascular access, Hemodialysis, Recirculation
Keywords: İç Hastalıkları_Hemşirelik